Development Changes in the Physicochemical Composition and Mineral Profile of Red-Fleshed Dragon Fruit Grown under Semi-Arid Conditions - Akath Singh; Saurabh Swami; Nav Raten Panwar; Mahesh Kumar; Anil Kumar Shukla; Youssef Rouphael; Leo Sabatino; Pradeep Kumar (Agronomy, 2022)
Red-fleshed dragon fruit offers an array of bioactive compounds. Its cultivation is gaining momentum in India, including in arid and semi-arid conditions. Among various factors, the fruit developmental stages and climatic conditions of locations greatly influence the biosynthesis and actual contents of different bioactive compounds and mineral contents of the fruit. The changes in physical attributes, and bioactive and mineral content in red-fleshed dragon fruit grown in semi-arid conditions in India were assessed and quantified at six developmental stages. Significant changes occurred in the physical attributes of the fruit and the bioactive compounds and mineral content during the fruit maturation stages of the red-fleshed dragon fruit. The fruit physical characteristics, such as fruit size, fruit and pulp weight gain, peel thickness, and fruit firmness, along with eating quality parameters, such as soluble solids, sugars, acidity and soluble proteins, were observed at optimum at 35 days after anthesis (DAA). The decrease in total phenolics (29.96%), total flavonoids (41.06%), and vitamin C (75.3%) occurred throughout the fruit development stages, whereas the content of betalains, which was detected initially at 25 DAA, increased (48.6%) with the progression of the fruit development stages. However, the antioxidant capacity and free radical scavenging activity demonstrated variable trends throughout the fruit maturation period. There was an increasing trend in all the minerals up to 35 days, followed by a slight decrease, except for phosphorus content, which increased until the last stage of evaluation. The colour characteristics, in conjunction with the bioactive and antioxidant potential determined in the present study, suggest that red-fleshed dragon fruit can be harvested at 35 DAA for long-distance transportation, and from 35 to 40 DAA for local marketing.